Case Report: De novo DHX37 mutations in Saudi patients with 46,XY differences of sex development - Alabduljabbar, Abeer; Abid, Sara; Farooq, Dania; Aljazaeri, Sara; Khamag, Yara; Alhuthil, Raghad; Alfahad, Latifah; Alsagheir, Afaf (Frontiers in Endocrinology, 2025)
Differences of sex development (DSD) are a group of congenital conditions involving atypical chromosomal, gonadal, or anatomical sex development. DHX37, a gene involved in ribosome biogenesis, located on chromosome 12, at the 12q24.31 region, has recently emerged as a contributor to 46,XY DSD, particularly gonadal dysgenesis and testicular regression syndrome (TRS). This study presents a case series from Saudi Arabia highlighting novel and known DHX37 variants in three patients with 46,XY DSD. Three Saudi patients presented with ambiguous genitalia, non-palpable or atrophic testes, and hypergonadotropic hypogonadism. Identified variants included two known (p.Arg308Gln, p.Arg674Trp) and one novel (p.Gly478Val) missense mutation. Phenotypic variability ranged from complete testicular regression to partial gonadal dysgenesis. Thus, this is the first case series of DHX37-related DSD in Saudi Arabia, expanding the mutational spectrum and reinforcing the gene’s role in testicular development. Genetic testing, particularly whole-exome sequencing, is essential for accurate diagnosis and management, especially in regions with high consanguinity.